(untitled) - Stojaník, Filip; Beranová, Jana (Aura musica, 2014)
The study is concerned with the presence of Czechoslovakian theatres in German-speaking countries in the sixties. In selected theatres such as Semafor and Rokoko, the aim is to capture the phenomenon of specific theatres' foreign tours; in comparison with Semaphore and Rococo however, black Theatre is captured through the viewpoint of actress and moderator Sylva Daníčková. For chequered choice, the work also includes the fate of actress Zdenka Procházková, who became very successful in Germany. From witnesses' memories, preserved theatrical criticisms and reviews it is clear that the Czechoslovakian culture, which was at the time very strong, didn't just have success at home but was also popular abroad.
Keywords: theartical hosting; musical theatres; Federal Republic of Germany; Czechoslavak artists; the sixties; achievements of Czechoclovak culture